Pendidikan: Kunci Keadilan Sosial - Tunisa, Resti Latipa; Asbari, Masduki; Ahsyan, Diyaul; Utami, Ulan Rizki (Journal of Information Systems and Management (JISMA), 2024)
The purpose of this discussion is to describe education in Indonesia as the key to social justice because quality and equitable education can open up equal opportunities for every individual to achieve prosperity and equal treatment. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to the oral narrative from Anies Baswedan's YouTube channel entitled "Education is the Key to Social Justice" presented by the Governor of DKI Jakarta, Mr Anies Baswedan. Explains that social justice must be realized because of one of the principles or principles of the ideology of the Indonesian nation, Pancasila. As a principle, it should have a higher position than the constitution. Therefore, all regulations and policies made by the state must contain values ​​deduced from these principles.